Green Technologies: technological prospection for soil improvement - Silva, André Luiz Gomes da; Macedo, Alice Costa; Martins, Viviane Souza (Cadernos de Prospecção, 2024)
The current global scenario of environmental crisis requires countries to invest in and encourage the search for sustainable alternatives to meet population demands, including food production. Technological research into so-called Green Technologies is therefore a priority in order to provide strategies that are less degrading to nature in agricultural activities. In view of the above, this study set out to analyze green patents aimed at sustainable agriculture. To this end, the Espacenet tool was used, detailing the steps used to arrive at the results of the 85 patent families dealing with its subject. As a result, it was found that the technologies developed within the scope of the study are concentrated in China and that this country has a lot to offer Brazil in terms of finding such solutions, serving as a benchmark. It was also concluded that Brazil, as a major world power in food production, needs to consolidate sustainable agricultural production strategies in order to meet the UN’s 2030 agenda.